2013
DOI: 10.1115/1.4024180
|View full text |Cite
|
Sign up to set email alerts
|

Method for Determining Instantaneous Temperature at the Surface of Combustion Chamber Deposits in an HCCI Engine

Abstract: Homogeneous charge compression ignition (HCCI) combustion is widely regarded as an attractive option for future high efficiency gasoline engines. HCCI combustion permits operation with a highly dilute, well mixed charge, resulting in high thermal efficiency and extremely low NOj, and soot emissions, two qualities essential for future propulsion system solutions. Because HCCI is a thermokinetically dominated process, full understanding of how combustion chamber boundary thermal conditions affect the combustion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Heat transfer from the combustion gas was dictated by the Woschni convection correlations, while heat transfer between structures and to thermal sinks (oil and coolant) was specified through individual convection coefficients. Calibration of these convection coefficients was performed utilizing measurements in the literature [25][26][27][28] in addition to unique measurements taken through similar means in the experimental study. More details on this model are in prior publications by Andruskiewicz et al 1…”
Section: Analytic Methodologymentioning
confidence: 99%
“…Heat transfer from the combustion gas was dictated by the Woschni convection correlations, while heat transfer between structures and to thermal sinks (oil and coolant) was specified through individual convection coefficients. Calibration of these convection coefficients was performed utilizing measurements in the literature [25][26][27][28] in addition to unique measurements taken through similar means in the experimental study. More details on this model are in prior publications by Andruskiewicz et al 1…”
Section: Analytic Methodologymentioning
confidence: 99%
“…Piston and head surface temperatures throughout the cycle could be compared to experimental data taken by Guralp et al 22 The original measurements of multiple piston and a single head location were obtained for four data points and were processed using the same experimental data analysis routines used to calibrate the thermodynamic model for consistency. Woschni's heat transfer correlation was modified according to the method described in Chang et al 23 to ensure applicability to homogeneous charge compression ignition (HCCI).…”
Section: Twts Model Calibration With Experimental Datamentioning
confidence: 99%
“…Previous studies have shown that deposits on combustion chamber surfaces can have a significant effect on the response of surface thermocouples [23,24]. As the deposit layer increased in thickness, it added thermal mass and decreased the response time of the sensor.…”
Section: Characterization Problem Statementmentioning
confidence: 99%
“…The effects of deposits on instantaneous temperature and heat flux measurements in HCCI engines have been studied extensively by Güralp et al [23,24]. They utilized coaxial thermocouples with a vacuum deposited surface junction to measure piston surface temperatures.…”
Section: Parametric Effects On In-cylinder Temperatures and Heat Tranmentioning
confidence: 99%
See 1 more Smart Citation